PENGARUH MODELDISCOVERY LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS VIII - NEZA ZAKIYA ARILI (Departemen Matematika, 2018)
The ability of problem solvingof mathematics is one of the learning objectives that are expected to be achieved by students. However, the problem solvingof mathematics of SMPN 2 Pantistudents is not as expected. An alternative solution is to implement the DiscoveryLearning model. The purpose of this research was to describe the differences in problem solvingof mathematics between the students who studied using the Discovery Learning model and those who studied using the conventional learning model of SMPN 2 Pantitowards mathematics. The type of research is quasi-experimental and descriptive, with a Randomized Control-Group Only design. Sampling was conducted by using simple random sampling technique, and VIII 3 as the experimental class and VIII 4 as the control class. The research instrument used a test to measure the ability to understand the mathematical problem solving in the form of essay. Based on the results of data analysis, problem solvingof mathematics of the students who took part in learning using the discovery learningmodel is better than the students who studied with conventional learning model. It means that the discovery learningmodel has a positive effect on the students’problem solvingof mathematics Keywords –Ability Of MathematicalProblem Solving,Discovery Learning Model